Pengaruh Campuran Sampah Plastik dengan Katalis Alam terhadap Hasil Produk Pyrolisis - Nuryosuwito, Nuryosuwito; Soeparman, Sudjito; Wijayanti, Widya; Sasongko, Mega Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Currently, various methods have been developed to overcome the problems caused by garbage. Pyrolysis is one methode of waste processing which is considered to be prospective enough to be developed. It?s because some advantages such as high conversion ratio and high energy content and potency as an alternative fuel in the future. Therefore, in this paper characteristics of pyrolysis will be studied. The waste materials used are catalyst and plastic waste. The resultant products of the pyrolysis process analyzed by Gas Chromatography / Mass Spectroscopy (GC / MS), while the thermal decomposition analysis was performed using Thermo Gravimetric Analysis (TGA). The results of pyrolysis process in isothermal conditions of a single component and a mixture of plastic waste and natural catalyst show that the final temperature of pyrolysis and the rate of heating affects to the distribution of pyrolysis products for all samples. As pyrolytic temperatures increase, liquid and gas products increase, while solid products tend to decrease. In the temperature range of 300°C, 400°C, 500°C, 600oC pyrolysis temperature with a heating rate of 100°C / min is the ideal temperature for obtaining the pyrolysis product of the liquid fraction and and the maximum gas fraction for all waste types studied.